A Simple Drug Delivery System for Platelet-Derived Bioactive Molecules, to Improve Melanocyte Stimulation in Vitiligo Treatment - Karolina Vocetkova; Vera Sovkova; Matej Buzgo; Vera Lukasova; Radek Divin; Michala Rampichova; Pavel Blazek; Tomas Zikmund; Jozef Kaiser; Zdenek Karpisek; Evzen Amler; Eva Filova (Nanomaterials, 2020)
Vitiligo is the most common depigmentation disorder of the skin. Currently, its therapy focuses on the halting of the immune response and stimulation of the regenerative processes, leading to the restoration of normal melanocyte function. Platelet-rich plasma (PRP) represents a safe and cheap regenerative therapy option, as it delivers a wide spectrum of native growth factors, cytokines and other bioactive molecules. The aim of this study was to develop a simple delivery system to prolong the effects of the bioactive molecules released from platelets. The surface of electrospun and centrifugally spun poly-ε-caprolactone (PCL) fibrous scaffolds was functionalized with various concentrations of platelets; the influence of the morphology of the scaffolds and the concentration of the released platelet-derived bioactive molecules on melanocytes, was then assessed. An almost two-fold increase in the amount of the released bioactive molecules was detected on the centrifugally spun vs. electrospun scaffolds, and a sustained 14-day release of the bioactive molecules was demonstrated. A strong concentration-dependent response of melanocyte to the bioactive molecules was observed; higher concentrations of bioactive molecules resulted in improved metabolic activity and proliferation of melanocytes. This simple system improves melanocyte viability, offers on-site preparation and is suitable for prolonged topical PRP administration.